2011
DOI: 10.1038/nm.2426
|View full text |Cite
|
Sign up to set email alerts
|

Follicular regulatory T cells expressing Foxp3 and Bcl-6 suppress germinal center reactions

Abstract: Foxp3+ regulatory T (Treg) cells suppress different types of immune responses to help maintain homeostasis in the body. How Treg cells regulate humoral immunity, including germinal center reactions, is unclear. Here we identify a subset of Treg cells expressing CXCR5 and Bcl6, and localized in the germinal centers in mouse as well as human. The expression of CXCR5 on Treg cells depends on Bcl6. These CXCR5+Bcl6+ Treg cells are absent in thymus but can be de novo generated from CXCR5-Foxp3+ natural Treg precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
1,277
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 948 publications
(1,320 citation statements)
references
References 37 publications
35
1,277
7
1
Order By: Relevance
“…By regulating initial CD4 + T‐cell activation and differentiation FoxP3 +  CD4 + Treg cells can reduce the initial generation of Tfh cells, although they may also enhance CD4 + T‐cell differentiation into Tfh cells by sequestering IL‐2 234. However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
See 2 more Smart Citations
“…By regulating initial CD4 + T‐cell activation and differentiation FoxP3 +  CD4 + Treg cells can reduce the initial generation of Tfh cells, although they may also enhance CD4 + T‐cell differentiation into Tfh cells by sequestering IL‐2 234. However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241. Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
See 1 more Smart Citation
“…T FH cell-like features can also be exhibited by other subsets of T cells, including regulatory T (T reg ) and invariant natural killer T (iNKT) cells. [24][25][26][27] In particular, recent studies have described a population of follicular T regulatory (T FR ) cells that share the phenotypic characteristics with T FH and T reg cells. Like classic T FH cells, the so-called T FR cells express high levels of CXCR5 and PD-1, and require Bcl6, SAP and CD28 for their development, but they express Foxp3 and can inhibit the GC reactions, similar to T reg cells.…”
Section: Characteristics Of T Fh Cellsmentioning
confidence: 99%
“…T FR cells are considered to be produced de novo from the progenitors of CXCR5 2 Foxp3 natural T reg cells. [25][26][27] Interestingly, the expression of T FH cell-like phenotype is not just confined to conventional T cells. Chang et al 24 recently identified a subset of iNKT, iNKT FH , cells that share phenotypic, functional and ontological characteristics of T FH cells.…”
Section: Characteristics Of T Fh Cellsmentioning
confidence: 99%